2019
DOI: 10.1021/acs.jnatprod.8b00988
|View full text |Cite
|
Sign up to set email alerts
|

Relative Configurational Assignment of 4-Hydroxyprorocentrolide and Prorocentrolide C Isolated from a Benthic Dinoflagellate (Prorocentrum lima)

Abstract: Herein, we clarify the structure and relative configurations of two prorocentrolide analogues (1 and 2) isolated from the benthic marine dinoflagellate Prorocentrum lima. The results of NMR spectroscopy show that 1 is prorocentrolide substituted by a hydroxy group at C-4, while the newly isolated compound 2 can be thought of as 1 lacking one ether ring and having one extra double bond. The relative configurations of all stereogenic centers and the configurations of the double bonds in 1 and 2 were determined u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…However, the biological activities of prorocentrolide analogs remain undetermined. Our research team has recently reported the cytotoxicities of 4-hydroxyprorocentrolide and prorocentrolide C, a new prorocentrolide analog derived from cultured P. lima dinoflagellates [15]. To the best of our knowledge, the mechanism of action of prorocentrolides as a toxin has not been previously investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the biological activities of prorocentrolide analogs remain undetermined. Our research team has recently reported the cytotoxicities of 4-hydroxyprorocentrolide and prorocentrolide C, a new prorocentrolide analog derived from cultured P. lima dinoflagellates [15]. To the best of our knowledge, the mechanism of action of prorocentrolides as a toxin has not been previously investigated.…”
Section: Discussionmentioning
confidence: 99%
“…In the ongoing search for bioactive toxins from cultured P. lima, recently, 4-hydroxyprorocentrolide (1) and prorocentrolide C (2) were reported, with demonstrated cytotoxicity against HCT-116, Neuro-2a, and HepG2 cells [15] (Figure 1). However, whether these prorocentrolide analogs induce apoptosis remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…For example in P. lima cultures, OA and DTX analogs, as well as formosalides, prorocentrolides and related macrolides, limaol and other non-characterized toxins have been reported (Table 1), however, their significance and biosynthesis have not yet been explored. Prorocentrolides and related macrolides are minor but unique constituents of P. lima and they should be considered chemotaxonomic markers (Torigoe et al, 1988;Lu and Chou, 2002;Lee et al, 2019;Li et al, 2020). Prorocentrolides are known as "fastacting toxins" and have been reported to act on nicotinic acetylcholine receptors (Molgó et al, 2017;Amar et al, 2018).…”
Section: Toxic Bioactive Metabolites Frommentioning
confidence: 99%
“…Prorocentrolides are known as "fastacting toxins" and have been reported to act on nicotinic acetylcholine receptors (Molgó et al, 2017;Amar et al, 2018). Prorocentrolide C exhibited cytotoxicity against cancer cells in vitro (HCT-116 and Neuro-2a cells) (Lee et al, 2019) as well as 4-hydroxyprorocentrolide (inhibitory activity against human colon adenocarcinoma DLD-1 and human malignant melanoma RP-MI7951) (Lu et al, 2005). Formosalides and limaol has also shown cytotoxicity activity against tumor cell lines (hepatocellular carcinoma, colon adenocarcinoma, neuroblastoma and T-cell acute lymphoblastic leukemia cells) (Lu et al, 2009;Yang et al, 2017).…”
Section: Toxic Bioactive Metabolites Frommentioning
confidence: 99%
“…Several benthic dinoflagellate species, including Ostreopsis, have been reported as potential causative agents of toxic poisoning in Korean coastal waters [30][31][32][33][34][35]. Recently, a rapid increase in the O. cf.…”
Section: Introductionmentioning
confidence: 99%